Six novel connexin32 (GJB1) mutations in X-linked Charcot-Marie-Tooth disease. - Lee, M; Nelson, I; Houlden, H; Sweeney, MG; Hilton-Jones, D; Blake, J; Wood, N; Reilly, M (2002)
X-linked Charcot-Marie-Tooth disease (CMTX) is a clinically heterogeneous hereditary motor and sensory neuropathy with X-linked transmission. Common clinical manifestations of CMTX, as in other forms of Charcot-Marie-Tooth disease (CMT), are distal muscle wasting and weakness, hyporeflexia, distal sensory disturbance, and foot deformities. Motor nerve conduction velocity is reduced. In male patients it is often less than 38 m/s in the median nerve (a value often used to distinguish between "demyelinating" and "axonal" forms of CMT), but in female patients conduction velocity may be faster than this or normal. Mutations in the connexin32 (gap junction protein beta 1 (GJB1)) gene are responsible for the majority of CMTX cases. This report describes six British CMTX families with six novel mutations (four missense, one nonsense, and one frame shift) of the GJB1 gene. Affected members in these six families had typical signs of CMT but in some affected members of three families there was additional central nervous system involvement or deafness in the absence of any other explanation other than CMT.